Capillary electrophoretic methods for the screening and determination of pharmacologic adulterants in herbal‐based pharmaceutical formulations. Issue 21 (7th October 2014) - Moreira, Ana Paula L.; Martini, Mariele; de Carvalho, Leandro M.; McCord, Bruce
<x xml:space="preserve">Abstract</x> This review aims to describe the CE methods utilized for the determination of adulterants in herbal‐based formulations marketed for different therapeutic purposes. The CE methods for screening and determination of pharmacologic adulterants are reviewed on the basis of the CE techniques and their detection methods. CZE and MEKC methods coupled to optical (UV), capacitively coupled contactless conductivity, and MS detection modes are discussed and reviewed. Worldwide adulteration cases related to pharmaceutical formulations containing herbs as the main active products are presented covering all the works published in the last four decades.